PROBIOTICS AS NUTRIENT SUPPLEMENT IN ARTIFICIAL FEED OF GOLD FISH (CARASSIUS AURATUS) - Sinha, Archana; Ghosh, Shubhadeep; Singh, Dharmender (Journal of Indian Fisheries Association, 2015)
The efficacy of three feeds incorporated with different probiotics - Lactobacil, Vizylac and Cyfolac as nutrient supplement was evaluated in an ornamental fish, Carassius auratus (Linn.). The basal diet (40% protein) was prepared and the probiotics were incorporated at different levels viz. Lactobacil at 8 x 107/100g and 12 x 107/100g, Vizylac at 8 x 107/100g and 12 x 107/ 100g and Cyfolac at 12 x 107/100g. Feeding trial was conducted for a period of 4 weeks. At the end of the experiment, bio-growth parameters and proximate composition of the fishes were studied. The growth, survival and protein content were improved in all the probiotic fed fishes compared to control. The maximum growth (0.74 g) and survival (85%) were observed in fishes fed with Lactobacil at 12 x 107/100g. It emphasizes that supplementation of feed with probiotics has a positive impact on the growth, survival and the body composition of goldfish. Keywords: Gold fish, probiotics, nutrient supplement